2016
DOI: 10.1002/ldr.2651
|View full text |Cite
|
Sign up to set email alerts
|

Applying the USLE Family of Models at the Sparacia (South Italy) Experimental Site

Abstract: Soil erosion is a key process to understand the land degradation, and modelling of soil erosion will help to understand the process and to foresee its impacts. The applicability of the Universal Soil Loss Equation (USLE) at event scale is affected by the fact that USLE rainfall erosivity factor does not take into account runoff explicitly. USLE‐M and USLE‐MM, including the effect of runoff in the event rainfall–runoff erosivity factor, are characterized by a better capacity to predict event soil loss. The spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 61 publications
(110 reference statements)
0
24
1
Order By: Relevance
“…For the 22‐m‐long plots, K MB S MB values calculated by Equation with b 1 = 1.45 were plotted against the steepness s and the following relationship was fitted to the data (Bagarello, Ferro, & Pampalone, , ; Di Stefano et al, ; Figure ): KMBSMB=ao[]exp()bs1 …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…For the 22‐m‐long plots, K MB S MB values calculated by Equation with b 1 = 1.45 were plotted against the steepness s and the following relationship was fitted to the data (Bagarello, Ferro, & Pampalone, , ; Di Stefano et al, ; Figure ): KMBSMB=ao[]exp()bs1 …”
Section: Resultsmentioning
confidence: 99%
“…As expected, among the three theoretically comparable USLE‐type models, USLE performed worst (Table and Figure ). The comparison between USLE‐M investigated by Di Stefano et al () and USLE‐MB showed that the two models have generally similar statistically performances even if the USLE‐MB yielded a maximum discrepancy factor between predicted and measured soil loss values (176) that was much lower than that of USLE‐M (291).…”
Section: Comparing Usle Usle‐m and Usle‐mb Performancesmentioning
confidence: 94%
See 2 more Smart Citations
“…Soil losses were quantified in various Mediterranean landscapes by using erosion plots [26][27][28][29][30][31]. The results of these studies have provided important reference outcomes that have had a fruitful repercussion in a range of related disciplines, such as ecology, geomorphology, and hydrology [32,33]. However, monitoring of soil erosion phenomena is often restricted to a few years of observations only, implying that the measurements are not necessarily representative of middle-term fluctuations occurring in ecosystems, especially under a Mediterranean climate [34,35].…”
Section: Introductionmentioning
confidence: 99%